A learning community within nursing practice: The value created by the activities and interactions during the early stage of community development. (November 2021) - Heemskerk, W.M.; Dauphin, S.L.M.; van Dorst, M.A.; Bussemaker, M.; Wallner, C.
Abstract: Aim/objective: This study examines the value that learning community activities and interactions produce (immediate value) during the early stage of community development, contributing to scientific insights on value creation. Background: Due to the rapidly changing healthcare landscape, nurses and nursing students need to adjust their skills, knowledge and collaboration with colleagues and other disciplines. Learning communities are a promising approach to enhancing professional growth and collaboration, where members find value through participation in the community. Design: For the study, a qualitative design was used. Methods: A secondary analysis of case study data, collected during the first five sessions of a hospital learning community comprised of nurses, nursing students and a nurse lecturer, was conducted. Results: The analysis revealed immediate value related to five themes: participation, activity, engagement, interaction, and confidence/trust. Members were encouraged to participate in and be involved during activities and interactions, such as asking questions, sharing their experiences and receiving feedback. Members became more familiar and confident in later community sessions, promoting immediate value creation. This was indicated by the different members who became active, took initiative or discussed problems. Conclusions: It is concluded that the activities and interactions produce value during the early stage of community development but may also grow to include new activities and interactions associated with further community development. Highlights: Learning communities are a promising way to integrate nursing and education. Activities and interactions involved in starting a learning community produce value. This value can be identified by different indicators, such as member participation. This value can be promoted through increased familiarization and confidence.